Bimbingan Karir Bagi Siswa SMK Sebagai Persiapan Memasuki Dunia Kerja - Elpika Yenes; Afdal Afdal; A Muri Yusuf (Indonesian Counselor Association (IKI), 2021)
This article describes the preparation of vocational students when carrying out career guidance to enter the world of work. The purpose of career guidance is to obtain information about the right type of further education so that the chosen career is in accordance with the talents, interests, and values that are upheld. So that students will not experience difficulties in making decisions with career plans that will be chosen for their future. The research method used is a literature review which is supported by data from various sources of articles, source books, and other supporting documents. The results of the analysis show that career guidance is very useful for vocational students to prepare for later entering the world of work. Therefore, students are expected to be able to apply the career guidance material provided by the counselor so that they are not confused in choosing a career later.